2013
DOI: 10.1111/ijn.12193
|View full text |Cite
|
Sign up to set email alerts
|

The effect of individual education on patients’ physical activity capacity after myocardial infarction

Abstract: The present study aims to determine the effects of individual education and counselling given to first-time myocardial infarction patients, including its effect on compliance with treatment. The sample comprised 90 patients, 45 in the intervention and 45 in the control group, selected by sequential sampling from first-time myocardial infarction patients. Data were collected between April and November 2008 by means of patient information form, International Physical Activity Questionnaire, 6 min walk test, Modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 33 publications
0
24
0
3
Order By: Relevance
“…Six studies met the inclusion criteria, 26–31 four were focused on patients with ACS 26–28 31 and two were focused on patients with stable CAD. 29 30 All were single-country studies from Australia, 26 Canada, 30 Malaysia, 27 Spain, 28 Turkey 31 and the USA. 29 The studies included a total sample size of 2831 patients, with a mean sample size of 472 (range 62–1757) patients and a mean of 75% men per study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies met the inclusion criteria, 26–31 four were focused on patients with ACS 26–28 31 and two were focused on patients with stable CAD. 29 30 All were single-country studies from Australia, 26 Canada, 30 Malaysia, 27 Spain, 28 Turkey 31 and the USA. 29 The studies included a total sample size of 2831 patients, with a mean sample size of 472 (range 62–1757) patients and a mean of 75% men per study.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of interventions were based on treatment education and counselling, 26 28 29 31 with one being delivered by community pharmacists, 26 one by physicians, 28 one by nurses 29 and one by the study researchers themselves. 31 Only one of the education and counselling studies referred to a specific intervention methodology, namely motivational interviewing.…”
Section: Resultsmentioning
confidence: 99%
“…Fizinio krūvio metu didėja deguonies poreikis miokarde, todėl pagerėja periferinė kraujotaka širdies vainikinėse kraujagyslėse, padidėja širdies susitraukimo jėga. Visa tai padeda didinti ligonio ištvermę, dėl kurios pagerėja fizinio krūvio toleravimas (Uysal, Ozcan, 2015). Miokardo infarkto gydymui taikoma kineziterapija antruoju reabilitacijos etapu vis dažniau pabrėžiama ir akcentuojama.…”
Section: įVadasunclassified
“…4 The goal of TPE is to improve health outcomes, including by preventing avoidable complications. 5 In prior studies, investigators have reported the positive impact of TPE on knowledge, behavioral, psychosocial, and health outcomes [6][7][8][9][10][11] ; however, there is a gap in understanding how TPE mechanisms impact specific self-management outcomes (eg, cardiac condition or disease clinical indicators and health behaviors). Furthermore, it is unclear what strategies are useful to address TPE barriers (eg, health literacy, cognition).…”
Section: Tpe Interventions For Self-managementmentioning
confidence: 99%